2009
DOI: 10.1021/jp906318n
|View full text |Cite
|
Sign up to set email alerts
|

Simple Route for Preparing Optically Trappable Probes for Surface-Enhanced Raman Scattering

Abstract: Surface-enhanced Raman scattering (SERS) has proven to be a powerful technique for a wide range of topics such as chemical analysis, materials research, and biological imaging. In this work, we report in detail on the development and characterization of micrometer-sized dielectric beads with metal colloids attached to their surface. The metalized beads were sufficiently transparent enabling optical trapping while the presence of metal islands provided the SERS. This method is fast and simple and is void of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…107,109,[114][115] Svedberg et al reported on SERS from optically trapped silver nanoparticles (R ≈ 40 nm) functionalized by a layer of thiophenol molecules, which both act as a SERS probe and lowers the electrostatic repulsion between particles to enable aggregation. 43 Single silver particles were optically manipulated to pair up with immobilized particles, which resulted in an increase of the SERS signal by a factor of 20 or more.…”
Section: Surface Enhanced Raman Spectroscopy Of Optically Trapped Metmentioning
confidence: 99%
“…107,109,[114][115] Svedberg et al reported on SERS from optically trapped silver nanoparticles (R ≈ 40 nm) functionalized by a layer of thiophenol molecules, which both act as a SERS probe and lowers the electrostatic repulsion between particles to enable aggregation. 43 Single silver particles were optically manipulated to pair up with immobilized particles, which resulted in an increase of the SERS signal by a factor of 20 or more.…”
Section: Surface Enhanced Raman Spectroscopy Of Optically Trapped Metmentioning
confidence: 99%
“…One successful approach is trapping with a laser with a frequency significantly different from the localized surface plasmon resonance . In another approach, transparent particles can be metalized to create optically trappable SERS probes …”
Section: Applications For Biological Samplesmentioning
confidence: 99%
“…During the last decade, optical tweezers were successfully combined with surfaceenhanced Raman spectroscopy (SERS), a highly sensitive technique for chemical analysis. [1][2][3][4][5][6][7][8] SERS relies on local field enhancement due to plasmon resonances at nano-sized metal structures (present in colloidal suspensions 9,10 or on solid SERS substrates [11][12][13] ), which leads to manifold Raman signal enhancement from molecules located near the metal surface. [14][15][16][17] There are two approaches reported in the literature for combining optical tweezers with SERS detection.…”
mentioning
confidence: 99%
“…Second, to assure transparency of the spheres (needed for successful trapping), the admissible extent of metal coverage is Page 3 of 37 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 limited. 4,7 The mentioned problems are eliminated using the microstructures proposed in this paper.…”
mentioning
confidence: 99%